Review of the Kangaroo competition-2010 - Mačys, Juozas Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2010)
The most interesting tasks of the Lithuanian Kangaroo competition-2010 are considered.